Face Recognition for an Attendance System - Daniel Pamungkas; Frederik Mahardika (International ABEC, 2021)
In the pandemic era, the attendance system needs to be contactless. Moreover, this system needs to be more automatic compare to the existing systems. This paper introduces the visual system using face recognition. The Haar cascade method and Local Binary pattern histogram algorithm is used to recognize the user’s identity. To capture the face, a webcam is used. This system enables detection and identifies the users. It also stores the time that check-in and checks out of the users automatically. The proposed system adequate to detect face up to 55 cm in the low lighting condition. Furthermore, this system enables to detection of multiple users in one frame.